FUTURE ENGINEERS PROFESSIONAL TRAINING IN STEM EDUCATION CONDITIONS: CHALLENGES AND PROSPECTS - Kokarіeva, Angelika (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The important aim of this study, in the preparation of future engineers, is developing an effective educational and professional program for the training of future engineers in STEM education, which combines theoretical knowledge with practical skills and promotes the development of such key competencies as critical thinking, the ability to self-study, adaptation to new technologies and innovative teaching methods. The program should also integrate the development of soft skills, such as communication, leadership, teamwork and project management, which are necessary for the successful professional engineers activity in modern conditions. The main goal of this study is to analyze the current challenges and prospects for the professional training of future engineers in STEM education, as well as to identify effective educational technologies and approaches for the development of key competencies, in particular technical and soft skills. The study of the professional training of future engineers in STEM education used a comprehensive approach that includes several general scientific methods: the analysis of the literature helped us to identify the main theoretical aspects and key trends in the development of STEM education, as well as the role it plays in the formation of professional competencies of future engineers. Surveys and interviews with students and teachers provided valuable data on practical experience, attitudes towards new educational technologies and challenges faced by participants in the educational process. The case method allowed us to analyze real examples of integrating STEM education into curricula, which made it possible to assess the effectiveness of the implemented innovations. The use of the comparison method helped to identify the strengths and weaknesses of traditional and innovative approaches to professional training, which is important for developing more effective educational strategies. Modeling of educational technologies made it possible to assess their potential impact on the educational process and the training of engineers, which allows us to make predictions about the development of STEM education in the future. All these methods together allowed us to gain a deep understanding of current trends in the training of engineers and identify ways to overcome existing challenges. In conclusion, we suggest that STEM education has great potential in improving the professional training of future engineers, as it combines theoretical knowledge with practical skills, which allows students to solve real engineering problems effectively. However, this process is followed by certain challenges, in particular the need for developing critical thinking and the ability to adapt to new educational standards and technologies. The integration of soft skills is an important component of professional training, as it contributes to the development of communication and team skills, which are important for a successful career as an engineer. The introduction of the latest educational technologies, such as virtual laboratories, online courses and mobile applications, can significantly improve the quality of education. The prospects for the development of STEM education are in the continuous improvement of curricula, the integration of innovative technologies and the development of partnerships with industry to train engineers who are able to solve global problems and implement innovations.